Meta-analysis: Effect of problem approach and inquiry approach toward students’ cathematical critical thinking skill over the past 4 years - Dwijayanti, Ida; Nugroho, Aryo Andri; Pratiwi, Yogi Indah (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Several studies have been conducted to improve the critical-thinking ability through various models, including problem approach and inquiry approach. The purpose of this study is to analyze which model is the most influential to improve students' critical-thinking skills in the last 4 years of research. This type of research is a mixed-method (quantitative-qualitative which, involved 230 students in the classroom with the problem approach and 263 students with the inquiry approach. The data collection technique used was the documentation of research reports. The data analysis used was meta-analysis through effect size calculation and Z-test. The result shows that the problem approach has a greater influence on students' critical thinking skills than the inquiry approach. This is indicated by the average values of the effect size and Z-test respectively 0.9685 and 83.122 for the problem approach and 0.7207 and 77.162 for the inquiry approach.